2022
DOI: 10.1002/ppul.26150
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound assessment of pulmonary edema in neonates with chronic lung disease before and after diuretic therapy

Abstract: Introduction: Bronchopulmonary dysplasia (BPD) is characterized by lung injury with varying degrees of disrupted alveolarization, vascular remodeling, inflammatory cell proliferation, and pulmonary edema. Diuretics are often used to ameliorate the symptoms or progression of BPD. Our primary objective was to use lung ultrasound (LUS) to determine if diuretics decrease pulmonary edema in infants with BPD. The secondary objective was to assess changes in respiratory support during the first week after initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In this study US showed Sn and Sp for diagnosis of pulmonary edema of 100% for both with total agreement of 100% with X-ray. This is in agreement with Kasniya et al (16) who showed the similar results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study US showed Sn and Sp for diagnosis of pulmonary edema of 100% for both with total agreement of 100% with X-ray. This is in agreement with Kasniya et al (16) who showed the similar results.…”
Section: Discussionsupporting
confidence: 93%
“…As regard pulmonary edema features by ultrasound, the current study showed that the main features were presence compact B lines without consolidation and normal pleural line in 100% of cases. This is in accordance with Kasniya et al (16) who studied 51 infants with evolving CLD on invasive O2 therapy and revealed that the number of B lines has been closely connected with the severity of pulmonary edema, and that utilising LUS by the detection of "B lines diagnose neonates with pulmonary edema has been demonstrated to be more sensitive and with greater NPV than X-rays. "…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we found a decrease in pulmonary edema after diuretic treatment. Recently, a case–control study using a modified score also showed that diuretic use is associated with decreased pulmonary edema and improved oxygenation in infants with CLD during the first week of treatment ( 29 ). Further prospective research needs to be conducted to explore LUS score progression after diuretic treatment as a suitable biomarker of CLD development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were associated with an improvement in oxygenation, respiratory rate, and CO 2 . Kasniya et al, 6 the single contribution from the USA, from Cohen Children's Hospital, gave us a nice example of “B‐lines” in preterm infants born at 24–30 weeks GA, who were on CPAP or nasal canula for evolving BPD. These infants were divided into a control group (no diuretics) and diuretic group.…”
Section: Progress In Neonatal Lung Ultrasound (Lu)mentioning
confidence: 99%